ENVIRONMENTAL EDUCATION: TEACHING AND RECYCLING ORGANIC WASTE ON PIPA-TIBAU DO SUL BEACH/RN (Editora Impacto Científico, 2025)
Due to technological advances, the population is changing and increasing its consumption habits, favoring the high production of waste. The waste produced by society increases more and more nowadays and brings in its composition several divergent characteristics. Some are half-reversible, others are completely toxic. In this way, waste ends up contributing to a series of environmental, health, economic and social problems. Solutions to problems arising from the generation of urban solid waste are becoming more complex every day, as there is a need to seek technological alternatives for the appropriate management of this waste, always taking into account social, economic and cultural changes in society. However, these problems can be minimized, faced with calm, planning, participation and awareness. Environmental education in Brazil today is perceived as a tool/instrument of contribution in the school context to minimize future impacts caused by actions of misdirection of waste. From this perspective, in order to provoke new cultural changes in relation to the environment, it is expected that new actions to implement environmental education in schools will favor new cultural habits in the local population in Tibau do Sul, with a specific focus on Praia da Pipa-RN, known as “Pipa”, in addition to housing native founders of the locality who in turn reside with different new forms of cultures arising from the foreignness present in the community. It is also a reference heritage, as it houses fauna and flora reserves of vital importance for the environment, such as the Pipa Ecological Sanctuary, Mata da Pipa State Park (PEMP), the Orla de Tibau do Sul Faunistic Reserve (REFAUTS), and the Bonfim-Guaraíras Environmental Protection Area. Therefore, this work aims to present solutions developed to improve the final disposal of organic solid waste, through educational and environmental guidelines, which will lead students to become citizens aware of their duty towards nature and thus be able to contribute to the preservation and development of the environment.DOI: https://doi.org/10.56238/edimpacto2025.090-068